Burkholderia Cepacia, an Emerging Nosocomial Pathogen in Neonates - Maria Shaikh, Humera Shaikh, Farhan Khan, Durga Devi, Kiran Memon, Sambreen Zameer, Kiran Aamir, Aamir Ramzan, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the prevalence of burkholderia cepacia infection at neonatal intensive care unit at Liaquat University Hospital Hyderabad/ Jamshoro. Study Design: Retrospective study Place and Duration: Department of Pathology Diagnostic and Research Laboratory LUMHS, Hyderabad. August 2017-September 2018. Methods: Total 140 neonates were presented in this study. Each case's blood sample was extracted and prepared for five days of incubation on the BACT ALERT 3D at 37 degrees Celsius. Blood culture-verified BCC infections were examined in this investigation within the first 72 hours of admission. Analysis has been done on the nosocomial B. cepacia pattern's antibiotic susceptibility. All data was analysed using SPSS 23.0. Results: There were 85 (60.7%) females and 55 (39.3%) males among all cases. Neonates mean age was 9.25±4.31 days. Most of the neonates had normal mode of delivery 90 (64.3%) and C-section was in 50 (35.7%) cases. According to antibiotic susceptibility in our study, most sensitive antimicrobial agents were Piperacillin/tazobactam 98%, Meropenem 98%, Minocycline 85% and Cefotaxime 80% and resistant agents were resistivity of Amikacin 99%, Ampicillin 99%, Cefixime 95% and Aztreonam 90%. Conclusion: This study revealed the high prevalence of Burkholderia cepacia infection in neonatal intensive care unit patients, and urgent need for an effective Intervention to control this outbreak. Keywords: Burkholderia cepacia, Neonates, Antibiotic susceptibility, Nosocomial infection